Coal Pillar Strength Formula in Indonesian coal mines - Ratih Hardini Kusuma Putri (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2020)
In underground coal mines, coal pillars play a major rule in sustaining the weight of the overburden and protecting the stability of the entries and crosscut during mine development and production, allowing the miners to safely extract the coal¹. The determination of a coal pillar size is adjusted to the expected load and strength of the coal seam. It needs to consider several factors such as pillar load (stress within the pillar), pillar strength, and safety factors. In this determination, an analysis will be conducted using five similar coal pillar strengths including; Obert-Duvall Equation (1967), Holland Equation (1964), Holland-Gaddy Equation (1956), Salamon-Munro Equation (1967), and Bieniawski (1983). Using AirLaya seam as an example, we can combine the results of various equations. The coal used in the Airlaya research area has a value of k = 425.75, thus the strength of Airlaya insitu seam coal is estimated to be 161,607 Psi.